2021
DOI: 10.3389/fpls.2021.781734
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Reactive Oxygen Species and Mitochondria in Seed Germination

Abstract: Seed germination is crucial for the life cycle of plants and maximum crop production. This critical developmental step is regulated by diverse endogenous [hormones, reactive oxygen species (ROS)] and exogenous (light, temperature) factors. Reactive oxygen species promote the release of seed dormancy by biomolecules oxidation, testa weakening and endosperm decay. Reactive oxygen species modulate metabolic and hormone signaling pathways that induce and maintain seed dormancy and germination. Endosperm provides n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 115 publications
2
34
0
Order By: Relevance
“…The HRG1/2 knockdown facilitated seedling growth whereas HRG1/2 overexpression significantly inhibited seed germination. The concentration of ROS in HRG1 overexpression was remarkably reduced as compared to HRG1/2 mutants after exposure to H 2 O 2 treatment in roots [87].…”
Section: Ros Generation and Signaling In Mitochondriamentioning
confidence: 88%
See 1 more Smart Citation
“…The HRG1/2 knockdown facilitated seedling growth whereas HRG1/2 overexpression significantly inhibited seed germination. The concentration of ROS in HRG1 overexpression was remarkably reduced as compared to HRG1/2 mutants after exposure to H 2 O 2 treatment in roots [87].…”
Section: Ros Generation and Signaling In Mitochondriamentioning
confidence: 88%
“…As H 2 O 2 production will induce damage to organelles, the resistance mechanism within the cell is initiated [84,85]. Two well-identified H 2 O 2 responsive genes (HRG1 and HRG2) that play role in H 2 O 2 production within the cell cause low disruption of the metabolic process [86,87]. In Arabidopsis, the signaling network for H 2 O 2 response gene 1/2 (HRG1/2) might immediately act endogenously or exogenously toward H 2 O 2 .…”
Section: Ros Generation and Signaling In Mitochondriamentioning
confidence: 99%
“…The current study assessed wheat performance for morphological traits involved in normal plant growth and production under drought stress conditions when vermicompost and organic manure was applied. Drought stress had a considerable negative impact on the wheat crop's performance when compared to the control, mostly through the generation of reactive oxygen species (ROS), which changed the leaf water potential, led to protein denaturation, and eventually impacted crop yield (Farooq et al, 2021). Due to a substantial reduction in cell turgidity and protoplasmic dehydration, prolonged drought also slows down plant development and crop yield.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria are one of the important sites of energy metabolism during seed germination. Analysis of mitochondrial gene dynamic changes confirmed that mitochondrial proteins with multiple functions, such as respiration, metabolism, and transport TCA cycle response proteins, are involved in seed germination [ 51 , 52 ]. In our experiment, transmission electron microscopy revealed that the structure of mitochondria was repaired after exogenous Spd treatment.…”
Section: Discussionmentioning
confidence: 99%